Analysis of Signalized Intersection Using MKJI 1997, PKJI 2023, and PTV VISSIM: Case Study in Pontianak - Putri, Hasanarrachmawati Arnie; Kadarini, S. Nurlaily; Mukti, Elsa Tri (Jurnal Teknik Sipil, 2025)
The rapid population growth in Pontianak has contributed to an increase in private vehicle usage, leading to increased traffic congestion, particularly at signalized intersections. One such problematic intersection is located at the intersection of Veteran Street, Gajahmada Street, Pahlawan Street, and Budi Karya Street, which serves as a central access point in and out of the city. This study aims to evaluate the performance of the intersection using the Indonesian road capacity analysis methods, MKJI 1997 and PKJI 2023, as well as the microscopic simulation software PTV VISSIM. Primary data, such as geometric design, traffic signal timing, traffic volume, and vehicle speed, were collected through field surveys and CCTV analysis. The results showed that the degree of saturation (DS) exceeded 0.85, indicating a need for immediate improvement. Several alternative solutions were proposed and analyzed, with the most effective being the combination of road widening on Veteran Street and conversion of Budi Karya Street into a one-way road with a three-phase signal cycle. This scenario successfully reduced DS below the critical threshold, improving overall intersection performance. The study demonstrates the importance of integrating analytical and simulation approaches for effective traffic management in urban areas.